Finding Moon - Hillerman, Tony (HarperCollins, 1995)
In his quest to unravel the threads left by his brother's death in Cambodia, Thomas Reed travels to the streets of Manila and the jungles of Cambodia, where he gradually pieces together the information that will lead him to his brother's lost child.